Screening for plant growth promoting fungi and their ability for growth promotion and induction of resistance in pearl millet against downy mildew disease - Murali, M; Amruthesh, K N; Sudisha, J; Niranjana, S R; Shetty, H S (Journal of Phytology, 2012)
A total of forty nine plant growth promoting fungi (PGPF) were successfully isolated from the rhizosphere of various grass species in Karnataka State, India. All the PGPF isolates were tested for their ability to enhance pearl millet seed quality parameters and to induce resistance against downy mildew disease in pearl millet. Susceptible pearl millet seeds 7042S were treated with PGPFs conidial suspension (1 x 108 cfu ml-1) and barley grain inocula (BGI) at 5%, 10% and 20% concentrations. Only six isolates among the forty nine tested recorded significant (P < 0.001) enhancement of seed germination and vigor when compared with the untreated control. Of the PGPF, Penicillium sp. (UOM PGPF 27) at 5% (w/w) concentration recorded highest seed germination of 92% and 1701.9 seedling vigor. The in planta colonization of the six PGPF isolates determined successfully in re-isolating the fungus from the basal root segments of 6 cm and 4 cm plated on PDA plates and also from the rhizosphere serial dilution of 10 3 to 10 5. Among the PGPFs tested in two modes, in BGI treatments, Penicillium sp. (UOM PGPF 27) at 5% (w/w) and Pythium sp. (UOM PGPF 41) at 10% (w/w) showed maximum disease protection of 67% and 61% respectively against downy mildew disease of pearl millet In case of conidial suspension treatments Penicillium sp. (UOM PGPF 27) and Trichoderma sp. (UOM PGPF 37) recorded highest disease protection of 71% and 66%, respectively under greenhouse conditions. Thus, the present study suggests that the tested PGPF, both as BGI inocula and conidial suspensions, can be used for pearl millet downy mildew disease management and also for plant growth.